Quantitative analysis of foraminifera and sedimentology of the marine Pliocene of Vale Farpado (Pombal, West Portugal) and its palaeoenvironmental interpretation - Pai, Mahima Praveen (2021)
Foraminifera occupy a large geological range from the Cambrian to the present day. They are excellent proxies to environmental changes due to their high abundance, well-preserved shells and short response time to changing environmental conditions. Planktonic foraminifera are also excellent markers of geological age as some species have a very specific age range. Sedimentology is the study of sediments such as clay, slit and sand and sedimentary rocks in general. Sedimentology aims to derive information on the depositional conditions of sediments. The outcrop sampled is located in Vale Farpado, near Carnide village, in the municipality of Pombal of West Portugal, and belongs to the Carnide Formation. The deposit is mainly Pliocene in age and its basal contact with the Amor Formation is a disconformity representing a stratigraphic lacuna from the middle Miocene to the lower Pliocene. Nine layers of the outcrop namely, 2bottom, 2a, 2b, 2c, 3, 4a, 4b, 5a & 5b were sampled and only seven (2bottom-4b) of them yielded fossils. Sedimentological analysis was carried out for all the samples except for 2bottom and 2a since these samples had too much organic matter and could not be processed in time. It showed that the sediments are poorly sorted and extremely asymmetrical. There is an upward increase of smectite which reaches a maximum at layer 4b. Fifty- eight species of benthic foraminifera and 11 species of planktonic foraminifera were identified. The dominance of Cibicides, Lobatula, Elphidium and the presence of mostly smooth and striate forms of Quinqueloculina concludes the environment to be high energy, cool temperate carbonate shelf sea. The occurrence of Globigerinella obesa in all the layers and the presence of Globigerinella pseudobesa (4.37-5.20Ma) in some indicates that early Pliocene (Zanclean age) could not be excluded. However further research in this regard is required. Globigerinoides diminutus remobilized by the erosion of the Miocene deposits can be found in layers 2bottom and 4a. It indicates the age of the Miocene sediments could be within N7-N9 zone (14.24-17.54Ma), late Burdigalian-Langhian age, in accordance with previous dating of this unit based on vertebrates MN5 (17-15Ma).